Patient-centered medical home and the quality of primary care: survey study with patients and administrators of community healthcare centers in Shanghai, China - Hua Jin; Huining Zhou; Leiyu Shi; Hanzhi Zhang; Aizhen Guo; Sen Yang; Shuoyuan Tan; Yuqing Shao; Dehua Yu; Jianwei Shi (BMC Primary Care)
Abstract Background Despite the widely acknowledged importance of primary care, there remains a significant gap in its comprehensive evaluation in China, particularly from the dual perspectives of institutional performance and patient experience. Objective We utilized two internationally recognized tools, the Primary Care Assessment Tool (PCAT) for measuring primary care quality from the perspective of patients and The Patient-Centred Medical Home (PCMH, emphasizing providing comprehensive, accessible, and high-quality healthcare services, addressing the evolving needs of patients while enhancing the efficiency and effectiveness of primary care systems) for assessing an organization’s primary care achievement, to evaluate whether institutional achievement in primary care correlates with better patient experiences in community healthcare centers (CHCs) in Shanghai, China. Methods Nine CHCs were randomly selected using a multi-stage sampling method, followed by a random selection of patients. The PCMH tool was used for CHCs, while the PCAT was administered to patients. Multivariate logistic regressions were used to analyze the association between the PCMH status of the CHCs and the quality of primary care experienced by patients. Findings A total of 1,782 patients and 9 CHC administrators completed the PCAT and PCMH tools, respectively. Generally, higher PCAT scores were associated with higher PCMH scores. Compared with patients from Level 1 PCMH CHCs, those from Level 2 and Level 3 CHCs reported significantly better experiences in ongoing care (Level 2: OR = 4.57, P < 0.001; Level 3: OR = 4.54, P < 0.001), family-centeredness (Level 2: OR = 3.39, P < 0.001), and cultural competence (Level 2: OR = 4.27, P < 0.001; Level 3: OR = 2.83, P = 0.03). Conclusion The study validated PCMH as a robust framework for assessing primary care performance. Furthermore, it identified specific areas where CHCs can enhance the patient experience, particularly in the domains of Coordination (Information Systems), Care Coordination, and Care Transitions. These findings underscored the need for targeted interventions to strengthen these aspects of primary care delivery, ultimately improving patient outcomes and satisfaction.